Low BMI at age 20 years predicts gestational diabetes independent of BMI in early pregnancy in Japan: Tanaka Women's Clinic Study. Issue 1 (13th December 2012) - Yachi, Y.; Tanaka, Y.; Nishibata, I.; Sugawara, A.; Kodama, S.; Saito, K.; Sone, H.
<x xml:space="preserve">Abstract</x> Diabet. Med. 30, 70–73 (2013) Abstract Aims Maternal obesity and weight gain since early adulthood are known predictors of gestational diabetes in Western countries. However, their impact has not been evaluated well in Asia, where mean BMI levels are generally lower than in Western countries. We therefore examined the associations of BMI at age 20 years and BMI change since age 20 years with the risk of gestational diabetes in Japanese pregnant women. Methods Six hundred and twenty‐four consecutive pregnant women without recognized diabetes before pregnancy, whose initial obstetric clinic visit was before 13 weeks' gestation, were prospectively observed. Weight at age 20 years was self‐reported. Baseline height and weight measurements were obtained at the initial obstetric visit. Multivariate logistic regression analysis estimated the risk of incident gestational diabetes for BMI change since 20 years and BMI at age 20 years. Results Twenty‐eight women developed incident gestational diabetes. By multivariate logistic regression analysis that adjusted for maternal age, parity and baseline BMI, we observed a statistically significant inverse association between BMI at age 20 years and incidence of gestational diabetes (odds ratio 0.68, 95% CI 0.51–0.92). Similarly, when we assessed the association of BMI change since age 20 years, adjusted for maternal age and parity, BMI change was associated with an increased risk of gestational diabetes (odds ratio 1.26, 95% CI 1.03–1.53). When we focused on the threshold of risk of gestational diabetes, women with BMI at 20 years of less than 18 kg/m2 had a 6.30‐fold (2.26–17.59) greater risk than women with both BMI at age 20 years of 18 kg/m2 or more and BMI change since age 20 years of less than 1.85. Conclusions Both low BMI at age 20 years and BMI change since age 20 years were significantly associated with increased risk of incident gestational diabetes.